Numerical Simulation of Particle Deposition in Arterial Bifurcation via Lattice Boltzmann Method. (4th July 2022) - Yi, Houhui
Abstract : Arterial bifurcation plays a key role in cardiovascular system, so studying the characteristic of the blood flows near bifurcated arteries is of great importance in hemodynamics. The lattice Boltzmann (LB) model is used to observe the behavior of the particle deposition near the bifurcated artery. The mechanical quantity, including particle trajectories, velocities, and angular velocities, is studied numerically by LB simulations. The particle is prone to stasis as it is close to the wall of bifurcated vessel for small flow Reynolds number. Larger branch angle leads to higher possibility of particle stagnation. The numerical results are consistent with the clinical observation. The study provides a basis for understanding the mechanism of hemodynamics near bifurcations and will provide a research basis for clinical diagnosis and treatment of patients with atherosclerosis.